2021
DOI: 10.1021/acs.jced.1c00108
|View full text |Cite
|
Sign up to set email alerts
|

Viscosity, Interfacial Tension, and Density of Binary-Liquid Mixtures of n-Hexadecane with n-Octacosane, 2,2,4,4,6,8,8-Heptamethylnonane, or 1-Hexadecanol at Temperatures between 298.15 and 573.15 K by Surface Light Scattering and Equilibrium Molecular Dynamics Simulations

Abstract: This work contributes to the characterization of three binary liquid hydrocarbon-based mixtures via the determination of density, viscosity, and interfacial tension over the entire concentration range up to temperatures of 573.15 K. The oscillating-tube method, surface light scattering (SLS), and equilibrium molecular dynamics (EMD) simulations are applied to analyze the influences of chain length, branching, and hydroxylation on the aforementioned thermophysical properties. For probing these effects, the thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 63 publications
2
5
0
Order By: Relevance
“…Figure 7b compares the α p values of water and the buffer solution with those of four representative C 16 OH/W and C 16 OH + C 20 OH/W emulsions. As can be observed, the isobaric thermal expansivity increases with the content of dispersed fatty alcohol, which agrees with the fact that cetyl alcohol has a higher expansivity (α p = 7-8•10 −4 K −1 at 343 K [81,91]) than water.…”
Section: Discussionsupporting
confidence: 85%
“…Figure 7b compares the α p values of water and the buffer solution with those of four representative C 16 OH/W and C 16 OH + C 20 OH/W emulsions. As can be observed, the isobaric thermal expansivity increases with the content of dispersed fatty alcohol, which agrees with the fact that cetyl alcohol has a higher expansivity (α p = 7-8•10 −4 K −1 at 343 K [81,91]) than water.…”
Section: Discussionsupporting
confidence: 85%
“…MD techniques have been used to investigate the hexadecane in several works. It has already been shown that the temperature behavior of viscosity, density, and interfacial tension estimated with MD [29] for hexadecane correlates well with recent data [18,24]. Nonetheless, improving the efficiency of PCMs-based heat capacitors necessitates knowledge of the systems' thermal physical features.…”
Section: Introductionsupporting
confidence: 63%
“…On average, the deviations between EMD and DLS are 17% at x co 2 < 0.5 and 9.8% at larger x CO2 , not including D 11,EMD at x CO2 = 0.71 and T = 303 K. Further details are provided in the Supporting Information. For T = 303 K and x CO2 < 0.35, the calculation of D 11,EMD was not possible due to solidification of the mixture in the simulation box. , …”
Section: Resultsmentioning
confidence: 99%